LANGUAGE LEARNING STRATEGIES OF THE HIGH ACHIEVERS OF TOEFL JUNIOR TEST IN AN INDONESIAN ISLAMIC BOARDING SCHOOL: A CASE STUDY - Cahyo, Nanang Heri Setyo Dwi; Rachmajanti, Sri; Muniroh, Siti (English Review: Journal of English Education, 2024)
This study investigates the language learning strategies (LLSs) employed by high-achieving students in the TOEFL Junior Test within the context of an Indonesia Islamic boarding school. Motivated by Indonesia's lower rankings in literacy, particularly in English, as highlighted by the 2022 PISA results, this study aims to address the gap in understanding how students in this specialized educational setting approach LLSs. This study focuses on six high-achieving female ninth-grade students from SMP Al Izzah Islamic Boarding School Batu, identified as high achievers based on their superior TOEFL Junior Test scores and exceptional performance on the school’s English final test. Using a qualitative case study approach, data were collected through the Strategy Inventory for Language Learning (SILL) 7.0, semi-structured interviews, and document analysis. The findings reveal that high achievers predominantly employ metacognitive strategies, such as goal setting and self-monitoring, as well as compensation strategies to overcome language barriers. Cognitive strategies, particularly engaging with English media, play a significant role in their language acquisition, while memory strategies are moderately used for vocabulary retention. This research highlights the importance of self-discipline, time management, and a supportive learning environment with its accessible teachers and nurturing community, significantly enhances continuous learning and overall students’ well-being. The study recommends for future research to expand the sample size to other Islamic boarding schools from various regions with more samples and explore the long-term impact of these strategies on academic and professional achievements.